Cervical intraepithelial neoplasia. Clinical analysis - Tatiana V. Klinyshkova; Natalia B. Frolova (LLC "MEDIAFORMAT", 2023)
Cervical intraepithelial neoplasia (CIN) is the most relevant topic in cervicology due to the risk of progression to cervical cancer and its rejuvenation. The relationship of precancer with human papillomavirus (HPV) expands the range of examination in CIN. Modern approaches to the diagnosis and management of patients with CIN, including the possibilities of immunomorphology, are considered. A clinical examples of the management of a patients with HPV-associated CIN is given.